The narrow path: criminal laws in upholding the consumer rights to information for halal pharmaceutical goods - Abdul Aziz, Norazlina; Amin, Naemah; Ramli, Noriah; Zawawi, Majdah (2015)
Halal Pharmaceutical product has recently captured the attention of the consumer which makes it to be one of the important products sought by the consumer. The right to information requires the halal pharmaceutical to be attached with information that can ensure its halal status. This is in line with upholding the right to information for the consumers. Consumers are not able to exercise their right to choose when the information about the product is not sufficient. In responding to this issue, consumer protectionist explains that the trending consumerism requires the consumer to be informed decision makers in the marketplace. The current halal related criminal laws, confine the punishment to false description and expression of trade object which are seen as a narrow solution to govern many aspect of halal related offences. Thus, this study intends to analyse the halal related criminal laws in accommodating consumers’ right to information. This study adopts a qualitative research method engaging the doctrinal study using the content analysis approach on the relevant laws and regulations supported by data from semi-structured interview with JAKIM. The findings of this study provide insights to the legislator in reviewing the current halal related criminal laws.